Analysis and Comparison of Unsupervised Algorithms to Detect Student Dropout Risk - Romero Rodríguez, W. J. G.; García De La Rosa, L. A.; González Páramo, A. (RIIIT Revista Internacional de Investigación e Innovación Tecnológica, 2026)
The COVID-19 pandemic had significant repercussions across various sectors, with the education sector being one of the most affected. The inclusion, continuity, and timely graduation of students enrolled in higher education are among the priorities established in the General Education Law. To achieve this, strategies and measures must be implemented to promote student retention in higher education institutions. For this reason, one of the primary educational challenges is providing teachers with the necessary tools and resources to identify and refer cases involving violence, mental health concerns, and potential school dropout.Through the application of data mining techniques in education, it has been possible to predict academic performance, create predictive models for student retention, and define behavioral profiles. A review of the literature has shown that student dropout is influenced by multiple factors, such as academic, economic, and social variables. By utilizing clustering algorithms, more detailed information and insights into dropout patterns can be obtained, supporting informed decision-making in higher education.In this project, the indicators will be analyzed and defined to monitor the academic performance of students at the ITESG campus in two phases: first using all student features and then using only the relevant features to compare results. This dataset will be managed by an intelligent system that will use unsupervised artificial intelligence algorithms, such as k-means and fuzzy c-means (FCM), to cluster students and detect potential dropout cases, which can then be referred to the tutoring area. The results suggest that the FCM algorithm performs best for detecting students at risk of dropping out.The objective of this work is to analyze and compare the performance of the unsupervised algorithms for detecting students at risk of dropping out, using a dataset from the Instituto Tecnológico Superior de Guanajuato and considering both the full set of features and only the most relevant ones identified through statistical tests.
Keywords: k-means, fuzzy c-means, education, school dropout, classification, artificial intelligence.